A cancer cell specific targeting nanocomplex for combination of mRNA-responsive photodynamic and chemo-therapy. Issue 72 (23rd August 2017) - Zhang, Xiaolong; Tan, Xionghong; Zhang, Da; Liao, Naishun; Zheng, Youshi; Zheng, Aixian; Zeng, Yongyi; Liu, Xiaolong; Liu, Jingfeng
Abstract : Herein, a cancer cell specific targeting nanocomplex which combines photodynamic therapy with chemotherapy through precisely responding to the intracellular tumor-related mRNA is presented. Abstract : We have developed a cancer cell specific targeting nanocomplex which combines photodynamic therapy with chemotherapy through precisely responding to the intracellular tumor-related mRNA. The combined treatment of these two modalities showed significantly enhanced therapeutic effects on cancer cells.